A randomized pilot trial of a couple-based intervention addressing sexual concerns for breast cancer survivors. Issue 2 (4th March 2019) - Reese, Jennifer Barsky; Smith, Katherine Clegg; Handorf, Elizabeth; Sorice, Kristen; Bober, Sharon L.; Bantug, Elissa T.; Schwartz, Sharon; Porter, Laura S.
Abstract: The purpose was to test the feasibility, acceptability, and preliminary efficacy of a 4-session couple-based Intimacy Enhancement (IE) intervention addressing breast cancer survivors' sexual concerns delivered via telephone. Twenty-nine post-treatment breast cancer survivors reporting sexual concerns and their intimate partners were randomized (2:1) to the IE intervention or to an educational control condition, both of which were delivered by trained psychosocial providers. Feasibility and acceptability were measured through recruitment, retention, session completion, and post-intervention program evaluations. Couples completed validated sexual, relationship, and psychosocial outcome measures at pre- and post-intervention. Between-group effect sizes and 95% confidence intervals were calculated using the Hedges g. Data supported intervention feasibility and acceptability. For survivors, the IE intervention had medium to large positive effects on all sexual outcomes and most psychosocial outcomes. Effects were less visible for relationship outcomes and were similar but somewhat smaller for partners. The IE intervention demonstrated feasibility, acceptability, and promise in addressing breast cancer survivors' sexual concerns and enhancing their and their partners' intimate relationships and psychosocial well-being. Implications for Psychosocial Oncology Practice: The IE intervention demonstrated feasibility and acceptability, suggesting it could be well-received by breast cancer survivors with sexual concerns and their partners. Effects of the IE intervention on breast cancer survivors' sexual concerns and on their and their partners' intimate relationships and psychosocial well-being could not be attributed to therapist time and attention. Interventions that psychosocial providers can use to address breast cancer survivors' sexual concerns are important to the growing number of breast cancer survivors living for many years after their diagnosis.